ANALISIS MUTASI PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL PADA KEPEMIMPINAN BUPATI BOYOLALI SENO SAMODRO TAHUN 2014-2015 ( Studi Penelitian Pada Pejabat Eselon II di Lingkungan Kantor Pemerintah Kabupaten Boyolali ) - Siti Jamilatus Sa'diyah; Sulistyowati .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2016)
The existence of regional autonomy with decentralization gives more authoritytowards regional to mantain its household business. Head of regional has authority tomanage Human Resources (HR) or managing officialdom through Country CivilApparatus management which is regulated in Law No. 5 of 2014 contained CountryCivil Apparatus one of them is to do Civil Servants’s mutation. In doing mutation, ofcourse it is not surprisingly that it is thick of interest loads as the efforts to supportvision and mission implementation, program and loyalty to leader even sometimesbecomes defensive strategy to win the regional election. This research is to analyzecivil servants’s political mutation in structural position 2nd echelon in SenoSamodro’s leadership as Boyolali Regent whether appropriate with regulation or not.Based on Human Resource management theory or officedom management HasibuanMalayu overwhelms recruitment, selection, inauguration, and placing.Method of this research in answering problrms inthis research is qualitativedescriptive research by type of main data are words and action. Source of data whichwas found were from primary data and secondary data. Technique of data collectionin this research used documents method and interview to program organizer whichwere BKD Boyolali Regency, BAPERJAKAT, Selection Committee and mutatedparty in 2nd echelon. Technique of data analysis by using data reduction, data servingand concluding.Mutation of civil servants in structural position 2nd echelon which was regulated inLaw No. 5 of 2014 was a new and good regulation as a step to do mutationtransparantly by involving external party from academics and public figure.Remembering the strength of Boyolali Regent’s authority and interest as itsdeterminant.Results of this research later hopefully can give benefit for government to mantainand control the mutation implementation in order to produce professional civilservants, and appropriate with their track records and far from interest.